The Relationship Between Corporate Social Responsibility and the Knowledge Transfer as Sources for Shared Value Generation - Melo, Mary Fernanda de Sousa de (2018)
Corporate social responsibility (CSR) should be viewed strategically as a source for the generation of shared value, whether tangible or not, for the focal company and its stakeholders. Companies operating with strategic CSR have greater access to external knowledge. However, it is not clear how the relations between the focal company and its stakeholders are and what the impacts are. Thus, the aim is to analyze how socially responsible companies with different strategic approaches generate shared value through the transfer of resources and knowledge with their stakeholders. It was used polar cases and a qualitative approach, through interviews, desk research and discourse analysis. The main stakeholders identified were: local communities; government; R&D companies and; business customers. Companies transfer resources and knowledge to local communities and key stakeholders. The reverse also occurs. The stakeholders and companies analyzed to provide an example of a symbiotic relationship, where there are social development and generation of competitive advantage, reaching four levels: business, a community where this company operates, business clients and the environment. Even if they are in different positions in the supply chain, the relationships between the focal company and its stakeholders generate value in a win-win relationship, which implies that the CSR investment brings external and internal returns. The article contributes through the combination of different theoretical approaches to explaining the generation of value besides economic as a source of multilateral gains. Also, we have the synthesis figure and the theoretical-empirical propositions.